2017
DOI: 10.1007/s13238-017-0385-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondria in osteogenic, adipogenic and chondrogenic differentiation of mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) are progenitors of connective tissues, which have emerged as important tools for tissue engineering due to their differentiation potential along various cell types. In recent years, accumulating evidence has suggested that the regulation of mitochondria dynamics and function is essential for successful differentiation of MSCs. In this paper, we review and provide an integrated view on the role of mitochondria in MSC differentiation. The mitochondria are maintained at a relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
169
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(207 citation statements)
references
References 50 publications
6
169
0
4
Order By: Relevance
“…Recent studies have demonstrated the crucial roles of mitochondrial function in cellular energy metabolism and the multidifferentiation processes of MSCs (37,61). Differentiation is an energy-demanding process that relies on the overall quality and relative abundance of the mitochondrial population, including de novo synthesis of organelle components, formation of mitochondrial membranes, and division of preexisting mitochondria (62).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the crucial roles of mitochondrial function in cellular energy metabolism and the multidifferentiation processes of MSCs (37,61). Differentiation is an energy-demanding process that relies on the overall quality and relative abundance of the mitochondrial population, including de novo synthesis of organelle components, formation of mitochondrial membranes, and division of preexisting mitochondria (62).…”
Section: Discussionmentioning
confidence: 99%
“…The role of bioenergetics in influencing stem cell function is currently a hot topic in the stem cell field (3033), but the impact of cellular bioenergetics on MSC function in particular is currently underappreciated (34). Moreover, the metabolic response of MSCs to irradiation, especially when considering the initial metabolic remodeling, is as of yet unknown.…”
Section: Resultsmentioning
confidence: 99%
“…For example, high levels of ROS cause reduced proliferation, unexpected differentiation, aging, senescence, and apoptosis (Denu & Hematti, ). Physiological levels of ROS are strictly controlled in MSCs by changing the number of mitochondria, which generate ROS (Li, Gao, Chen, & Guan, ). In the undifferentiated state, MSCs have low numbers of mitochondria, while this number increases at the differentiated stage.…”
Section: Discussionmentioning
confidence: 99%